SINKRONISASI PERENCANAAN PEMBANGUNAN TOP-DOWN DAN BOTTOM-UP TENTANG PEMBANGUNAN AIR MINUM - Andi Setyo Pambudi (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
Drinking water is a basic human need that is always increasing along with the rapidly growing population. The drinking water sector requires a large investment in supporting the achievement of national development. For local governments, the development of drinking water infrastructure is constrained by limited APBD funding sources. Meanwhile, the demand for drinking water has become an urgent matter to be carried out as part of the state's mandate to fulfill basic services for the state. Special transfer funding through the Physical DAK is an attractive option for regions to meet this need. The analysis in this study uses a mixed method approach through a gap analysis based on a literature study of central-regional planning documents and questionnaires. This study aims to assess the relationship between top down and bottom up Physical DAK planning for regional development. The results of the analysis show that Central Java Province has received the largest Physical DAK budget for the Assignment of the Drinking Water Sector nationally, but has not fully allocated the drinking water sector in its development planning, especially for the issue of rural water supply. This shows that Central Java Province has not prioritized the drinking water program in its regional development so that it is not stated in the RKPD. Based on the results of the questionnaire, the implementation of DAK in Central Java has a positive output for improving drinking water services and SPM infrastructure. This is due to the proportion of the budget, implementation, and good supervision. Achievement of output and realization of time can be carried out according to the target. In the implementation of the DAK for Drinking Water Assignment in Central Java, compliance with the Regional Government Work Plan (RKPD) was 60 percent, while conformity with the Budget Implementation Documents – Regional Apparatus Work Units (DPA-OPD) was 66.7 percent.